Modeling Whale Deaths From Vessel Strikes to Reduce the Risk of Fatality to Endangered Whales - R. Cotton Rockwood; Jeffrey D. Adams; Sean Hastings; Jessica Morten; Jaime Jahncke (Frontiers in Marine Science, 2021)
Vessel strikes have been documented around the world and frequently figure as a top human cause of large whale mortality. The shipping lanes in the Santa Barbara Channel, California and nearby waters have some of the highest predicted whale mortality from vessel strikes in the United States waters of the eastern Pacific. Beginning in 2007, National Oceanographic and Atmospheric Administration requested voluntary vessel speed reductions (VSRs) for vessels greater than 300 GT traveling in the Santa Barbara Channel shipping routes to decrease whale mortality from ship strikes. We employed a ship strike model using whale density data and automatic identification system (AIS) vessel data to estimate mortality under several management scenarios. To assess the effect of the VSR on strike mortality, we bootstrapped speeds from vessels greater than 19 m long that transited when no VSR was in place. Finally, we calculated the predicted mortality for hypothetical cooperation scenarios by artificially adding speed caps post-hoc to real vessel transits. For 2012–2018, we estimated that in our study area on average during summer/fall (June–November) 8.9 blue, 4.6 humpback, and 9.7 fin whales were killed from ship strikes each year (13–26% greater than previously estimated). We evaluated winter/spring (January–April) humpback mortality for the first time, resulting in an estimate of 5.7 deaths on average per year. Poor cooperation with the VSR led to low (5% maximum) to no reductions in the estimated number of strike mortalities. Evaluating potential scenarios showed that if 95% cooperation occurred in the lanes, whale deaths there would decrease by 22–26%. Adding VSRs with similar cooperation levels at the northern end of the Santa Barbara Channel and south of Channel Islands National Marine Sanctuary could decrease estimated strike mortalities in those areas by 30%. If VSRs were added and cooperation reached 95% there and in the lanes, we estimate a 21–29% decrease in vessel strike mortalities could be attained relative to ...